THE INFLUENCE OF INTEGRATED MARKETING COMMUNICATION, ISLAMIC SERVICE QUALITY AND HANDLING COMPLAIN ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE - Wijayanti, Nofi Tri; Nabila, Rifda (Sharia Business Management UIN Raden Intan Lampung, 2024)
This research adopts a quantitative research type in analyzing the influence of integrated marketing communication, Islamic service quality and complaint handling on customer loyalty with customer satisfaction as an intervening variable. The population in this study were all customers of the State Savings Bank (BTN) Syariah KCP Ungaran. In determining the sample, the researcher used purposive sampling techniques and the Lemeshow formula to determine the sample size so that 100 respondents were obtained. In testing the hypothesis, this research applies multiple linear regression analysis and path analysis using SPSS 23 software. Based on the results of the hypothesis test, integrated marketing communication has a negative effect on customer loyalty. Islamic service quality has no effect on customer loyalty. Complaint handling has a positive effect on customer loyalty. Integrated marketing communication has no effect on customer satisfaction. Islamic service quality has a positive effect on customer satisfaction. Complaint handling has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive effect on customer loyalty. Customer satisfaction is unable to mediate the influence of integrated marketing communication on customer loyalty. Customer satisfaction is able to mediate the influence of Islamic service quality on customer loyalty. Customer satisfaction is unable to mediate the influence of integrated marketing communication on customer loyalty.